2018
DOI: 10.1007/s00253-018-9130-2
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological applications of occlusion bodies of Baculoviruses

Abstract: The ability of Baculoviruses to hyper-express very late genes as polyhedrin, the major component of occlusion bodies (OBs) or polyhedra, has allowed the evolution of a system of great utility for biotechnology. The main function of polyhedra in nature is to protect Baculovirus in the environment. The possibility of incorporating foreign proteins into the crystal by fusing them to polyhedrin (POLH) opened novel potential biotechnological uses. In this review, we summarize different applications of Baculovirus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
10
0
1
Order By: Relevance
“…The use of polyhedrin protein as a biotechnological tool has increased mainly due to the intrinsic capacity of selfaggregation [27]. In addition, we have shown that using only the first 110 amino acids of polyhedrin (PH ) retains the self-aggregation property [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of polyhedrin protein as a biotechnological tool has increased mainly due to the intrinsic capacity of selfaggregation [27]. In addition, we have shown that using only the first 110 amino acids of polyhedrin (PH ) retains the self-aggregation property [28].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most studied insect viruses that forms polyhedra is the Autographa californica multiple nucleopolyhedrovirus (AcMNPV) [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The use of polyhedrin protein as a biotechnological tool has increased mainly due to the intrinsic capacity of self-aggregation [27]. In addition, we have shown that using only the first 110 amino acids of polyhedrin (PH (1-110) ) retains the self-aggregation property [30].…”
Section: Discussionmentioning
confidence: 99%
“…Transfer vectors were obtained by cloning esat-6, cfp-10, and Rv3615c genes in NotI and SpeI restriction sites in the multiple cloning site of vector pFBDPOLH/POLH [López et al, 2018a]. The correct insertion of each gene in the final transfer vectors was confirmed by restriction enzymes and sequencing.…”
Section: Expression and Purification Of Polh-esat-6 Polh-cfp-10 Andmentioning
confidence: 99%
“…As an alternative, foreign genes can also be expressed as a fusion protein to polyhedrin. The advantage of this strategy is that the polyhedrin moiety in the fusion protein drives the localization of a heterologous antigen to an insoluble, crystalline protein matrix called polyhedron or occlusion body (OB), which facilitates the protein purification pro- cedures [López et al, 2018a]. Additionally, baculoviruses do not infect vertebrates and therefore no humoral or cellular immune responses would occur in vertebrates against baculovirus proteins.…”
Section: Introductionmentioning
confidence: 99%